Reproductive Coercion Among College Students: An Extension and Test of Routine Activity Theory - Hayes, Brittany E. (Violence against women, 2023)
The current study is guided by routine activity theory to explore the risk of experiencing reproductive coercion among a sample of sexually active college students (N = 1,515). Findings indicate that being in an exclusive relationship was associated with lower odds of reproductive coercion, yet prior victimization, including emotional abuse and sexual violence, was associated with higher odds of reproductive coercion. This study supports other research that finds reproductive coercion does not occur in isolation from other victimization experiences, and multifaceted prevention strategies are needed. Implications relating to autonomous reproductive decision-making are discussed.